The Inner Music in AlkiwaniAldimashki’s poetry (1795 AD, 1173 Hijri). (Damascus University Journal of arts and humanities sciences, 2022)
Reading the poetic texts of Alkiwani-Aldimashki presents rhythmic formats that reflect his poetic recognition. He recognizes that rhythmic roots are from the rectifiers of the creative poetic discourse and those roots are very close to the poetic experience. The research studies the text’s inner music with a special analysis and excludes its elements from his poems, it is clear through repetitions, homophone, epanalepsis and the antithesis. Through those figures of speech, the value of rhythmic poetic rhetoric appeared which full of semantic inspiration. The research studies a romantic poem that has a lot of musical elements and those elements in the romantic poem are the priorities according to the poet. It is difficult to find a poem without those musical elements combined with the other text’s components to perform the significance.His inner music with its sound gatherings and suggestive energy was matched to his psychological view and this music shows hidden meanings in the poet’s personality. Even the sentences in their various structures come compatible with the deep structure of the text by chanting some letters and some words.
Keywords: Music; kiwi poem; poem music; rhythm poem